The Effect of a Multimodal Approach in Audiovisual-Based Indonesian Language Learning at SDN Sondosia - Afifah Afra Amatullah; Mulyadi Mulyadi; Didit Haryadi; Syarifudin Syarifudin; Desy Ningsih Komalasari (FKIP - Universitas Riau, 2026)
Elementary school students’ text comprehension skills are still relatively low because classroom learning is often dominated by conventional verbal instruction with limited use of interactive learning media. The audiovisual-based multimodal approach is considered important to support students’ literacy development through visual and auditory representations. This study aimed to analyze the effect of a multimodal approach based on audiovisual media on elementary school students’ text comprehension skills. The research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The participants consisted of 30 third-grade students of SD Negeri Sondosia, including 16 students in the experimental class and 14 students in the control class. Data were collected through pretests and posttests. The findings revealed that the mean score of the experimental class increased from 68.3 in the pretest to 79.7 in the posttest, while the control class improved from 66.1 to 72.3. The independent sample t-test indicated a significant difference between the two classes in the posttest results (p = 0.009 < 0.05). In addition, the N-Gain score of the experimental class was higher than that of the control class. Therefore, the audiovisual-based multimodal approach can be considered an effective alternative strategy for enhancing elementary school students’ text comprehension skills.